Doing your research project : - Bell, Judith (Open University Press, 2006)
This book provides beginner researchers with the tools to do the job, to help them avoid some of the pitfalls and time-wasting false trails, and to establish good research habits. It takes researchers from the stage of choosing a topic through to the production of a well-planned, methodologically sound, and well-written final report or thesis on time. It is written in plain English and makes no assumptions about previous knowledge.